STUDY ON THE RELATIONSHIP BETWEEN GENDER AND ANXIETY IN TEAM SPORTS GAMES - Francisc Remus DATCU; Sorin BRÎNDESCU; Martin Petru DOMOKOS; Simona PETRACOVSCHI (Cluj University Press, 2022)
This study aimed to identify possible differences in competitive anxiety and whether there is gender variability. Methods: The study included a total of 118 female and male athletes aged 13-24 years from 3 sports: 62 football athletes (16-female; 46-male), 33 basketball athletes (16-female; 17-male) and 23 volleyball athletes (15-female; 8-male). All 3 groups were subjected to an assessment aimed at state anxiety. The following questionnaire was used for this assessment: Questionnaire for the identification of competitive state anxiety. Hypothesis: There are statistically significant differences in anxiety levels (cognitive and somatic) between athletes in the three sports involved in the research (football, basketball and volleyball). This study's results show statistically significant differences in competitive state anxiety among the study group, both genders and between the three categories of athletes (football, basketball, volleyball). Male subjects in this study tend to score higher to lower on competitive anxiety, compared to female subjects. Football players have lower levels of competitive state anxiety. Conclusions: There are differences in anxiety levels (cognitive and somatic).